The Effect of Lavender Therapeutic Scent Toward Sleep Quality for Elderly at Nursing Home - Zuriati .; Melti Surya (Faculty of Nursing, Universitas Andalas, 2018)
Background: Poor sleep quality in elderly can brings fatigue, poor concentration, and frequently sleep in the afternoon. There were 26 elderly that experiencing poor sleep quality at Nursing home. This condition can be countered by non-pharmacology which is using lavender therapeutic scent. Purpose: To find out the effect of lavender therapeutic scent toward sleep quality of elderly at Nursing home. Method: The type of this study was quantitative with quasi-experimental and two group pretest-posttest design, and T-test dependent as testing instrument. Sampling technique in this study was purposive sampling which was 26 respondents that divided into 13 respondents in intervention group and 13 respondents in control group. The study was conducted on January to July 2016. Data collection was conducted on 18th to 31st May. Results: Study finding was average score of elderly sleep quality before lavender therapeutic scent application was 15.23 and after application of lavender therapeutic scent was 5.54. Statistical testing result found p = 0.000 where it showed that there was an effect of lavender therapeutic scent toward improvement of elderly sleep quality. Conclusion: It was suggested to Nursing home to apply lavender therapeutic scent twice a week before sleep time in order to improve sleep quality of elderly.